2020
DOI: 10.1002/cche.10357
|View full text |Cite
|
Sign up to set email alerts
|

Flour and bread making properties of whole and split yellow peas treated with dry and steam heat used as premilling treatment

Abstract: Background and objectives Pulse flours can impart off‐flavors limiting their use in foods. The objective of this study was to examine the flour and bread making properties of whole and split yellow peas treated with dry and steam heat used as a premilling treatment. Findings Particle size distributions and pasting properties of flours milled from heat‐treated peas were altered, and starch damage was reduced compared to flours milled from untreated peas. Breads made with flour milled from heat‐treated peas had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 26 publications
7
13
0
Order By: Relevance
“…This was in accordance with Sopiwnyk et al. (2020), who reported significantly increased L * and reduced a * values in Revtech processed pea flours at 120°C with 0% moisture. Change in the color of pulse flours as a result of heat treatments has also been reported by Bourré et al.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This was in accordance with Sopiwnyk et al. (2020), who reported significantly increased L * and reduced a * values in Revtech processed pea flours at 120°C with 0% moisture. Change in the color of pulse flours as a result of heat treatments has also been reported by Bourré et al.…”
Section: Resultssupporting
confidence: 92%
“…Significantly higher a * (2.4) and b * (23.8) val-ues were obtained for RT 10%, indicating a more red and yellow hue compared to USYP and RT 0%. This was in accordance with Sopiwnyk et al (2020), who reported significantly increased L * and reduced a * values in Revtech processed pea flours at 120 • C with 0% moisture. Change in the color of pulse flours as a result of heat treatments has also been reported by Bourré et al (2019), Ma et al (2011), andYoung et al (2020).…”
Section: Proximate Analysissupporting
confidence: 92%
“…The pasting profiles of individual samples are reported in Figure 1B. Raw flour showed a significantly lower (p < 0.05) pasting temperature than the heat-treated sample Our findings are consistent with those reported for yellow pea [27]. In the previous study, a high viscosity was also associated with changes occurring to the protein fraction, that could form a network capable of retaining water and increasing the viscosity of the system.…”
Section: Structural Modifications Lead To Different Pasting Propertiessupporting
confidence: 89%
“…The higher viscosity observed in the heat-treated flour was likely due to the greater ability of starch to absorb and bind water. Nevertheless, changes in WHC can also be related to protein denaturation [27,42], as proteins, upon unfolding, expose previously hidden peptide bonds and polar side chains that contribute to their water-holding ability [43].…”
Section: Thermal Treatment Affects Water-holding Capacitymentioning
confidence: 99%
“…At higher levels of yellow pea flour inclusion (15 and 20%), significant increases in the development time and decreased stability of the dough were noted; this behavior is probably related to the dilution and interruption of gluten network continuity and/or gluten-legume protein interactions. In previous studies, significantly longer development times and decreased stabilities were also observed with the use of flours of raw and germinated pea at levels up to 15% [49], raw, germinated, and toasted yellow pea at 30% [50], raw and germinated yellow pea and faba bean at 10-20% [21], and raw and steam-processed pea and split pea at a level of 20% [19]. 1 Notation of samples as in Table 1.…”
Section: Empirical Rheological Parameters Of Yellow Split Pea Fortified Wheat-based Doughsmentioning
confidence: 93%